Recent legislation regarding the appointment of public school educators: the end of the decentralisation debate in education? - Johan Beckmann (Acta Academica, 2009)
After 1994 it was generally expected that the decentralisation of powers would give parents in school governing bodies significant power regarding the governance of schools concerning the  appointment of staff and recommendations for appointment. The South African Schools Act of 1996 appeared to meet these expectations. However, a number of amendments to the law since then have apparently diminished the powers of parents in this regard. This article analyses the powers parents received in this regard circa 1996 and the amendments effected since then, and argues that the recent changes do not necessarily mean an end to decentralisation.